Development of a Neutralization Assay for Influenza Virus Using an Endpoint Assessment Based on Quantitative Reverse-Transcription PCR - Teferedegne, Belete (Public Library of Science, 2013)
A microneutralization assay using an ELISA-based endpoint assessment (ELISA-MN) is widely used to measure the serological response to influenza virus infection and vaccination. We have developed an alternative microneutralization assay for influenza virus using a quantitative reverse transcription PCR-based endpoint assessment (qPCR-MN) in order to improve upon technical limitations associated with ELISA-MN. For qPCR-MN, infected MDCK-London cells in 96-well cell-culture plates are processed with minimal steps such that resulting samples are amenable to high-throughput analysis by downstream one-step quantitative reverse transcription PCR (qRT-PCR; SYBR Green chemistry with primers targeting a conserved region of the M1 gene of influenza A viruses). The growth curves of three recent vaccine strains demonstrated that the qRT-PCR signal detected at 6 hours post-infection reflected an amplification of at least 100-fold over input. Using ferret antisera, we have established the feasibility of measuring virus neutralization at 6 hours post-infection, a duration likely confined to a single virus-replication cycle. The neutralization titer for qPCR-MN was defined as the highest reciprocal serum dilution necessary to achieve a 90% inhibition of the qRT-PCR signal; this endpoint was found to be in agreement with ELISA-MN using the same critical reagents in each assay. qPCR-MN was robust with respect to assay duration (6 hours vs. 12 hours). In addition, qPCR-MN appeared to be compliant with the Percentage Law (i.e., virus neutralization results appear to be consistent over an input virus dose ranging from 500 to 12,000 TCID(50)). Compared with ELISA-MN, qPCR-MN might have inherent properties conducive to reducing intra- and inter-laboratory variability while affording suitability for automation and high-throughput uses. Finally, our qRT-PCR-based approach may be broadly applicable to the development of neutralization assays for a wide variety of viruses.